PROSES PEMBELAJARAN TEMATIK TERPADU DENGAN MODEL PROBLEM BASED LEARNING DI SEKOLAH DASAR - Eliyasni, Rifda; Anita, Yesi; Hanafi, Andre Satrio (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2020)
This research is based on the background that in integrated thematic learning, teachers have not involved students in linking learning with the real world of students. The purpose of this study is to describe the integrated thematic learning process with the Problem Based Learning model. The method used is classroom action research with qualitative and quantitative approaches. The results showed that the integrated thematic learning process increased after treatment was given from 78.57% to 96.42%.